SISTEM INFORMASI PERENCANAAN KEUANGAN SATUAN KERJA PENYUSUNAN ANGGARAN PER TAHUN PADA MADRASAH ALIYAH NEGERI 2 MUARO JAMBI BERBASIS WEB - Purnama, Fery; Wardani, Ary Kusuma (FORTECH (Journal of Information Technology), 2019)
This Financial Budget Planning Information System was created to convey information about annual financial budget planning at Muaro Jambi State 2 Islamic Madrasah. The purpose of this study is to find out and describe the presentation process which includes: Identifying activities and sources expressed in money, Developing budgets, revising budgets, approving budgets, approving budgets and implementing financial management principles in budgeting. Data collection methods used in preparing this final assignment are Observation, Library Studies and interviews. This program was developed using PHP and MySQL. In conclusion, the Financial Budget Planning Information System at Muaro Jambi State 2 Madrasah Aliyah has been completed using PHP and MySQL.